A case study: resistance training effect on muscle mass and body fat percentage among youth football players during fasting month - Nor Fazila Abd Malek (Tanjung Malim, 2023)
A case study: resistance training effect on muscle mass and body fat percentage among youth football players during fasting month by Nor Fazila Abd Malek